2021
DOI: 10.1007/s00405-021-07201-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acids, pepsin, bile acids, and trypsin on laryngopharyngeal reflux diseases: physiopathology and therapeutic targets

Abstract: Purpose Laryngopharyngeal reflux disease (LPRD) is a general term for the reflux of gastroduodenal contents into the laryngopharynx, oropharynx and even the nasopharynx, causing a series of symptoms and signs. Currently, little is known regarding the physiopathology of LPRD, and proton pump inhibitors (PPIs) are the drugs of choice for treatment. Although acid reflux plays a critical role in LPRD, PPIs fail to relieve symptoms in up to 40% of patients with LPRD. The influence of other reflux subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 94 publications
1
26
0
5
Order By: Relevance
“… 2 However, the pathogenesis of LPRD remains unclear, as it is a disease with multiple etiological factors. 3 …”
Section: Introductionmentioning
confidence: 99%
“… 2 However, the pathogenesis of LPRD remains unclear, as it is a disease with multiple etiological factors. 3 …”
Section: Introductionmentioning
confidence: 99%
“…One study has shown gastric reflux that reaches into the upper airway causing cellular damage in the epithelial lining and introducing chronic inflammation resulting in laryngopharyngeal malignant transformation [13]. Another study demonstrated reflux material such as hydrochloric acid, pepsin, bile, bile acids and trypsin inducing cellular proliferation, apoptosis and DNA damage all promoting carcinogenesis of the larynx and pharynx [14]. These pathogeneses may occur in the lower respiratory tract resulting in chronic inflammation thus contributing to the development of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Acid and bile reflux play a critical role-hydrochloric acid is a major cause of esophageal irritation and reflux symptoms causing injury to mucosal epithelial cells and inflammation. The abnormal secretion and activation of pepsin can also cause proteolysis and cell damage [13]. Pathohistological changes in the esophageal mucosa can be divided into three categories: nonerosive reflux disease, reflux oesophagitis, and Barett's esophagus [14].…”
Section: Etiology and Pathophysiology Of Gerdmentioning
confidence: 99%